KONSEP PENDIDIKAN ISLAM TENTANG MANUSIA DAN MEMULIAKAN MANUSIA - Nazaruddin (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Agama Islam YAPTIP Chadijah Ismail Pasaman Barat, 2022)
Education is a system and a way to improve the quality of human life in all aspectsof human life. Education is the most important part of human life which also distinguisheshumans from animals. Therefore, there are various views which state that education is acultural process to elevate human